SYNTHESIS AND RESEARCH OF SORBENTS BASED ON MELAMINFORMALDEHYDE RESIN - Yodgorov, Ravshan Abdimalik ogli; Kurbanov Faxriddin , Bobomurodovich; Khudoykulova, Gulbahor Ibrahim qizi; Primkulova, Maftuna Otkir qizi (Educational Research in Universal Sciences, 2023)
In this research, sorbents containing nitrogen and sulfur were synthesized based on melamine-formaldehyde resin. IR-spectroscopy was used for its structural description. The vibrational frequencies of the corresponding bonds in the theoretical data are determined to be consistent with the results obtained from the analysis of the IR spectrum, and an optical microscope image is presented.